How’s Prospect of Digital Banking in Indonesia? Notes From Islamic Views, Economic Value Added for Banking Industry, and Changing Costumer Behavior - Myrna Anggarani; Mohamad Soleh Nurzaman (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
This study aims describe prospects of digital banking in Indonesia. Digital banking has prospect of being able to increase value added for banks, and also change consumer behavior. Moreover, this study also explain how Islamic views to technological developments, especially the use of digital banking for customer’s financial needs. The development of digital banking is important for banking industry. Digital banking has emerged to make transaction easier for customers and to get access to various financial information. This study uses descriptive qualitative analytic methods. Data collection uses documents in the form of literature which related to the theme of the study.